2000
DOI: 10.1002/1097-0185(20001001)260:2<124::aid-ar20>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal density in the human retinal ganglion cell layer from 16–77 years

Abstract: Literature assessing whether or not neurons (retinal ganglion cells and displaced amacrine cells) are lost from the retinal ganglion cell layer in mammals with age is still controversial, some studies finding a decrease in cell density and others not. To date there have been no studies estimating the total number of neurons in the retinal ganglion cell layer of humans throughout life. Recent studies have concentrated on the macular region and examined cell densities, which are reported to decrease during aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 0 publications
5
31
1
2
Order By: Relevance
“…Neuronal density in the ganglion cell layer showed a mean reduction of 0.53% per year in this study. 35 The results of the presented study are also consistent with the clinical observation that morphologic glaucomatous damage frequently precedes visual field loss by several years. [36][37][38][39] Histologic studies confirmed that up to 40% of retinal nerve fibers might be lost before visual field defects occur.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Neuronal density in the ganglion cell layer showed a mean reduction of 0.53% per year in this study. 35 The results of the presented study are also consistent with the clinical observation that morphologic glaucomatous damage frequently precedes visual field loss by several years. [36][37][38][39] Histologic studies confirmed that up to 40% of retinal nerve fibers might be lost before visual field defects occur.…”
Section: Discussionsupporting
confidence: 88%
“…Even if the measured neuroretinal rim loss in the control group of the presented study is very low-data is comparable to large cross-sectional studies 8 and histologic examinations. 28,35 The results of the presented study support evidence for the presence of age-related neurodegeneration in the eye and might change the view of interpretation of morphometric change in the context of determination progressive disease.…”
Section: Discussionsupporting
confidence: 61%
“…The studies based on axon counts [3,30,32,36,43] generally indicate lower age-related losses than those based on cell body counts [7,19], probably arising from differences in sampling strategies [14]. In addition, there is uncertainty in defining the slopes of the aging functions, because they are based on relatively few samples due to the formidability of obtaining suitable post-mortem material, and in many of the studies the variability across eyes was large.…”
Section: Introductionmentioning
confidence: 99%
“…28 We particularly investigated performance in the time window that is most relevant for natural visual tasks (within a few hundred milliseconds). Because normal aging may also affect the anatomical substrates involved in contrast adaptation [30][31][32] (such as a reduction in RGC density 30 ), and because neurological alterations contribute to contrast deficits in older adults, 33 an additional group of young observers were included in the study to investigate the effects of aging on rapid contrast adaptation.…”
mentioning
confidence: 99%